X-chromosome methylation in manifesting and healthy carriers of dystrophinopathies: concordance of activation ratios among first degree female relatives and skewed inactivation as cause of the affected phenotypes - Azofeifa Navas, Jorge (1995)
Artículo científico -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 1995. Este documento es privado debido a limitaciones de derechos de autor.